Late Holocene Ameghinomya antiqua shells from the Beagle Channel: A multi-proxy approach to palaeoenvironmental and palaeoclimatic reconstruction - Morán, Ariana Gisela; Bayer, María Sol; Beierlein, Lars; Martínez, Juan José; Benitez-Vieyra, Santiago Miguel; Mackensen, Andreas; Brey, Thomas; Gordillo, Sandra (Elsevier Science, 2021)
It is important to understand the historical precedents of current situations to be able to anticipate where the current global environmental and climatic change may lead. Geo-historical data provide information beyond the limitations of instrumental data. This study aims to reconstruct components of the palaeoclimatic and palaeoenvironmental history of the Beagle Channel (BC) during the Late Holocene by using Ameghinomya antiqua shells. We use fossil and modern shells in a comparative analysis through a multiproxy approach, i.e., shell morphometrics, shell growth, and stable oxygen isotope ratios. A holistic analysis of all the proxies indicates that higher productivity occurred around 3542 yr B.P. in the BC, evidenced by more significant growth, size, and longevity in fossil specimens. In addition, smaller ligaments, cardinal teeth, and the pallial sinus in fossil specimens indicate a low-energy environment typical of a marine archipelago. Lastly, palaeotemperatures are estimated to be warmer than today, although the intensity may be overestimated due to the freshwater inflow that would change the salinity of the BC waters. Further analysis in Late-Holocene shells is essential for a more detailed environmental reconstruction around the southern tip of South America.